2020
DOI: 10.3989/mc.2020.08619
|View full text |Cite
|
Sign up to set email alerts
|

Adapted ageing tests for the evaluation of alabaster used in the restoration of Bishop’s Palace of Tarazona

Abstract: The advanced condition of deterioration of the column’s bases of the courtyard of the Bishop’s Palace of Tarazona (Spain) built in the middle of 16th century required its restoration with Aragonese alabaster. Thus, adapted ageing tests were developed to simulate the environmental conditions in which the stones were and will be exposed. These tests were thermal fatigue by temperature variations, acid rain and water stagna­tion by immersion tests and a combination of both agents of decay. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The impact of water on the stone has led to mass losses on the stone surface and mortar voids between the joints in the Savur region, resulting in the problem of 'missing part'. Several studies have highlighted the detrimental effects of water on limestone-based materials, including surface erosion, mortar voids, and missing parts (Alves et al, 2021;Ergüler & Shakoor, 2009;Bustamante et al, 2020;Iucolano et al, 2019;Beck & Al-Mukhtar, 2014;Bonazza et al, 2017;Gulotta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of water on the stone has led to mass losses on the stone surface and mortar voids between the joints in the Savur region, resulting in the problem of 'missing part'. Several studies have highlighted the detrimental effects of water on limestone-based materials, including surface erosion, mortar voids, and missing parts (Alves et al, 2021;Ergüler & Shakoor, 2009;Bustamante et al, 2020;Iucolano et al, 2019;Beck & Al-Mukhtar, 2014;Bonazza et al, 2017;Gulotta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Beck & Al-Mukhtar (2014) observed that there is a significant erosion in the limestone with wetting-drying cycles. Bustamante et al, (2020) found a mass loss of more than 14% on stone surfaces that are heavily exposed to water. Winkler (1997) observed that the side exposed to rain shows significant erosion in stone structures, while the material is preserved on the protected side.…”
Section: Introductionmentioning
confidence: 99%
“…An example of significative mass redistribution was observed by Beck and Al-Mukhtar [67] with the formation by wetting-drying cycles of a calcite patine in limestone. Tests with alabaster (gypsum-rich material) performed by Bustamante et al [68] attained a mass loss slightly below 14% in conditions of immersion and shaking, using water with "natural" pH (i.e., the pH of water in equilibrium with atmospheric CO 2 without human contributions; pH = 5.6), which was prepared by mixing tap water (pH around 7) and distilled water (pH = 4.5). Visual observations in this last study showed some noticeable dissolution with clay-filled fissures developing a positive relief.…”
Section: Wettingmentioning
confidence: 99%
“…Other situations in the literature caused by the effect of water were reported as mass loss problems in stones exposed to cycles simulating sunlight, evaporation, condensation [15][16][17][18][19][20][21][22][23]. Lubera [24] reported six stone types (fine-grained conglomerate, breccia, limestone, sandstone, amphibolite, and two granites) in the study, with the effect of water about 6% in breccia samples, 0.5% in limestone and 4% in fine-grained conglomerate samples.…”
Section: Introductionmentioning
confidence: 99%